Teacher Mediation in an ESL Science Education Context - Yerra, Madhuri; Sarangapani, Padma M. (Voices of Teachers and Teacher Educators, 2019)
The widespread increase in English-medium schools across India including the emergence of the low fee paying/budget school sector places many students and teachers in a situation of subject teaching in what are effectively English as Second Language (ESL) contexts. Given the absence of language across the curriculum and ESL related preparation in preservice teacher education, interested teachers devise their own strategies to enable students to negotiate the dual requirements of language and subject learning. The present article is based on a case study that explores the practices a science teacher working in a charitable school in Hyderabad. The mediational practices are documented and explored in relation to the literature. Her dominant technique is found to involve bilingual meaning-making of concepts drawing on everyday contexts of students and developing their observation and reasoning. Her language focus emerges as the learning of the language of science rather than English per se. These practices compare well with the literature. The article concludes with reflections on the sources of this teacher’s practices, and proposes that her autobiographical experiences, her interest in science and understanding of the nature of science and finally her reflective practice account for these practices.